Review of Competition Law on Tariffs Lower Limit Indonesian Airlines - Dwi Desi Yayi Tarina; Imam Haryanto (Universitas Medan Area, 2021)
The price policy is an inseparable part of business competition. The price policy is not solely related to efforts to maintain prices or even control prices at a certain level but is an effort to generate profits that are proportional to social welfare. Since the entry of business competition regulations in Indonesia, with the increase in airline business actors, the competition between them has become more profitable for consumers. With high competition and competitive prices, airlines, especially national airlines, show that the target of this airline is the middle market share. In this paper, we will discuss the determination of the lower tariffs for air transportation issued in the Regulation of the Minister of Transportation of the Republic of Indonesia and regarding its application and impact on consumers and business actors in the aspect of business competition. Research result The stipulation of the lower limit rate stipulated in the Regulation of the Minister of Transportation Number 14 of 2016 is basically against the provisions of the business competition law, particularly about the prohibition on price-fixing as regulated in Article 5 Paragraph (1) of Law No. 5/1999. The effect of Regulation of the Minister of Transportation Number 14 of 2016 on airline business actors and consumers, among others, is that the freedom of business actors to determine their fares is reduced, this results in not achieving price efficiency.